Theory and Practice in the Choice of Social Discount Rate for Cost-Benefit Analysis: A Survey - Juzhong Zhuang; Zhihong Liang; Tun Lin; Franklin De Guzman (Asian Development Bank (ADB), 2007)
The choice of an appropriate social discount rate for cost–benefit analysis of public projects has long been a contentious issue and subject to intense debate among economists. This debate has gained new impetus from the recent discussions on the economics of climate change. The purpose of this paper is to survey theories and practices in the choice of the social discount rate. More specifically, the paper examines economic arguments for discounting future benefits and costs and analytical approaches to the choice of the social discount rate, including how a social discount rate can be estimated empirically under each approach; and policy practices followed by countries around the world in the choice of the social discount rate. This paper is intended as a reference material on project economic analysis for ADB staff, consultants, and concerned government officials in developing member countries.
hdl:11540/1853
Keywords: 330; Soziale Diskontrate; Kosten-Nutzen-Analyse; Theorie